Spare the Rod, Spoil the Society? - Hannah Sorenson (Journal of Contemporary Sociological Issues, 2021)
You have the opportunity to decide whether or not a person gets caned, the only caveat is that they have committed a crime against you. What will you do? This essay explores the moral complexity of caning in Singapore through an exploration of corporal punishment, criminal justice, moral philosophy, and the Asian values debate; a dilemma that ultimately places concerns of society and the individual at odds. In doing so, the essay argues that the morality of caning changes on the basis of the ethical framework and modification of situation variables. Even so, the moral complexity of caning is not superficially evident. In order to thoroughly engage with all elements of this complexity, this essay begins by attempting to decipher the place of punishment within international human rights frameworks. From there, the essay explores the morality of punishment and its employ in colonial endeavors. This leads to a discussion of modernization, humanitarian ideologies, and control. By creating a framework for analyzing criminal justice in Singapore—including an outline of the intersections of criminal justice, development, and prosperity —this essay seeks to explore the balance between corporal punishment as a tool of prosperity and corporal punishment as a source of pain and degradation. When placed in consequentialist and virtue-based ethical frameworks caning in Singapore looks very different, forcing the moral actor to weigh societal concerns with concerns for individual pain, suffering, and liberties. Keywords: Caning, Morality, Society, Punishment.